3D electro-anatomical mapping to guide conduction system pacing in complex cardiac anatomies. (14th October 2021) - Marcantoni, L; Pastore, G; Baracca, E; Pellegrini, N; Andreaggi, S; Bartolomei, M; Centioni, M; Rigatelli, G; Galuppi, E; Roncon, L; Zanon, F
Abstract: Background: Conduction System Pacing (CSP) includes both His Bundle Pacing (HBP) and Left Bundle Branch Pacing (LBBP). It guarantees physiological cardiac activation and it is essential to avoid pacing-induced dyssynchrony. Markedly dilated atria, up-grading to CRT, and congenital cardiopathies still represent complex anatomical scenarios in which the available tools could often result inadequate and graved by suboptimal results. Objective: To evaluate the feasibility and effectiveness of 3D electro-anatomical mapping (EAM) to guide CSP (both HBP and LBBP) in patients with characteristics that allows "a priori" classification as complex anatomical scenario with low probability of success using only fluoroscopic guidance and available tools. Left atrium area >40 cm 2 ; post-PICM up-grading and congenital heart disease were considered signs of anatomical complexity. Methods and results: The study includes 25 patients (19 males, mean age 76–11 years; mean baseline EF 34.2–12.6%; 17 BBB; 5 post-PICM up-grading), candidates for CSP. 16 and 9 were respectively implanted with PM and ICD (13/12 dual/three-chamber devices). CARTO system was used in 6 ptss and EnsiteTM Precision in 19. EAM involved reconstruction of the right atrium and sub-tricuspid septum with the use of a decapolar catheter. Several "tags" have been placed on the His signals, in order to reconstruct the "His Cloud" and distinguish within it the proximal, medium, and distal area (Fig. 1). The sub-tricuspid septum was always reconstructed so that intra-procedurally operator could easily move from HBP to LBBP based on electrical parameters or paced QRS morphology. The mapping catheter was removed after the mapping phase and replaced with the pacing lead. Both exposed fixed screw 3830 leads and standard stylet-driven leads were used. HBP was achieved in 10 pts and LBBP in 13 pts. Three failures were resolved by CS lead implant. The time spend for His cloud mapping was 18±7 min. The mean threshold was 1.1±0.5 V; sensing 11.6±9.3 mV and impedance 786±339 ohm. Baseline QRS 155±19 ms and paced QRS 119±7 ms. In cases of LBBP we were also able to measure on the EAM map the depth of the catheter within the septum, resulting in 11.5±3.1 mm and the distance of the initial screw site from the His of 26.5±10.3 mm. Conclusions: The electro-anatomical mapping allows the accurate reconstruction of "His cloud" by properly distinguishing proximal, middle, distal His. The sub-tricuspid zone of the interventricular septum is also reconstructed in high definition, so that intra-procedurally it is possible to easily move from HBP to LBBP and vice-versa based on the electrical parameters and paced QRS morphology. This method appears safe and effective even in complex cardiac anatomies possibly saving time and fluoroscopy use. The tags on the His cloud and sub-tricuspid septum can satisfactorily guide lead placement with high reproducibly. Funding Acknowledgement: Type of funding sources: None.